Multi-objective optimal planning for designing relief delivery systems - Tzeng, Gwo-Hshiung; Cheng, Hsin-Jung; Huang, Tsung Dow (Transportation research. Part E, Logistics and transportation review, 2007)
The fatal earthquake on September 21, 1999 caused significant damages to Taiwan, which made the national government focus on strengthening relief systems regarding natural disasters. Disaster prevention, protection, and reconstruction are the major areas of focus to reduce human suffering and damage from disasters. A key point is the ability to enhance the distribution of relief materials effectively. In this study, we construct a relief-distribution model using the multi-objective programming method for designing relief delivery systems in a real case. The model features three objectives: minimizing the total cost, minimizing the total travel time, and maximizing the minimal satisfaction during the planning period. The first two objectives pursue the efficiency goal, whereas the third pursue fairness – making best effort to ensure relief commodity delivery to all demand points. Results of an empirical study are presented and suggestions are given for future research.